2020
DOI: 10.3399/bjgpopen20x101033
|View full text |Cite|
|
Sign up to set email alerts
|

Uptake of direct oral anticoagulants in primary care: an ecological and economic study

Abstract: BackgroundClinical trials indicate that direct oral anticoagulants (DOACs) are as effective as warfarin at preventing ischaemic stroke. It is unclear, however, whether relative changes in DOAC uptake have affected clinical and economic outcomes in practice.AimTo investigate variations in DOAC uptake and the relationship with hospital admissions and cost.Design & settingAn ecological study using electronic administrative records from England, April 2012 to March 2017.MethodMultivariable regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Numerous studies have confirmed an increase in OAC prescribing over the last decade in the UK for prevention of stroke in AF in the general population [ 11 , 18 20 ] and to older people [ 21 ]. This change has also been observed at practice level, with general practices with a higher ratio of older people and a higher prevalence of AF more likely to prescribe DOACs [ 22 ]; however, there is a risk of ecological fallacy if wishing to extrapolate this practice level data to prescribing to individuals. Whilst some of the increase in prescribing of OACs may be due to the introduction of DOACs, it may also be attributed to the introduction of Quality Outcome Frameworks for AF which incentivised the diagnosis of AF and prescribing of anticoagulants [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies have confirmed an increase in OAC prescribing over the last decade in the UK for prevention of stroke in AF in the general population [ 11 , 18 20 ] and to older people [ 21 ]. This change has also been observed at practice level, with general practices with a higher ratio of older people and a higher prevalence of AF more likely to prescribe DOACs [ 22 ]; however, there is a risk of ecological fallacy if wishing to extrapolate this practice level data to prescribing to individuals. Whilst some of the increase in prescribing of OACs may be due to the introduction of DOACs, it may also be attributed to the introduction of Quality Outcome Frameworks for AF which incentivised the diagnosis of AF and prescribing of anticoagulants [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 88%
“…Historically, vitamin K antagonists (VKA) therapy has been the anticoagulant of choice to reduce the risk of stroke in patients with non-valvular atrial fibrillation (NVAF). 1 However, successful VKA therapy has important practical limitations, including regular monitoring of patients’ international normalised ratio (INR) due to variability of control. 2 , 3 The target INR range is 2–3 (unless otherwise indicated) 4–8 with net clinical benefit closely related to the proportion of time that INRs remain in this range [time in therapeutic range (TTR)].…”
Section: Introductionmentioning
confidence: 99%